Antonio Gramsci collaboratore del ‘Romanisches etymologisches Wörterbuch’ (con una cartolina inedita di Matteo Bartoli) (Atti del Sodalizio Glottologico Milanese, 2018)
In his youth, Antonio Gramsci was student at the University of Turin with a prominent interest for the linguistics, developed under the direction of the scholar Matteo Bartoli. An involvement of the young student in the editorial activity of the ‘Romanisches etymologisches Wörterbuch’ of Wilhelm Meyer-Lübke, more particularly in the revision of the Sardinian data, can be argued on the basis of two letters sent by Gramsci from Turin to the family in Sardinia. A new letter of Bartoli to Gramsci, dated in 1913 and presumably connected with such an activity, is here edited. KEYWORDS: Gramsci, Bartoli, Meyer-Lübke, history of linguistics, Romanisches etymologisches Wörterbuch